Perspektif Upaya Pencegahan Korupsi di Indonesia - Hendi Prihanto; Tamrin Lanori; Selfiani Selfiani; Yudhistira Adwimurti (Universitas Muhammadiyah Jakarta, 2023)
Objectives. This study aims to investigate and validate corruption prevention measures implemented in different government organizations, with a specific focus on the ministry institutions, employing various predictors, including religiosity, work culture, recruitment practices, job rotation, and governance, to assess their effectiveness in preventing corruption.Design/method/approach. The population and research sample consist of all ministries in Indonesia located in the DKI Jakarta area, selected through convenience sampling technique. The unit of analysis is the public officers known as Aparat Sipil Negara (ASN) working in the ministry head offices. Data was collected through questionnaire during October-December 2022. Data analysis involved descriptive statistics, tests on instrument quality, hypothesis testing, and multiple linear regression.Result/findings. The results indicate a positive and significant impact of variables such as religiosity, work culture, job rotation, and governance on corruption prevention. However, recruitment shows a negative and insignificant effect on corruption prevention.Theoretical contribution. The aspect of detecting, measuring, and implementing preventive measures for corruption is theoretically grounded in the variables used, which have not been previously explored in this specific context. These variables, such as work culture, job rotation, and recruitment, have been extensively studied by numerous researchers in other contexts, but their application to corruption prevention in this study is novel.Practical contribution. Recruitment can create opportunities for corruption; therefore, it is essential to conduct transparent and accountable selection processes.Limitations. The utilization of a questionnaire introduces certain limitations to the results, primarily due to potential conflicts of interest and inconsistencies among respondents. Additionally, the study also faces the constraint of a limited number of participants.